Environmental analysis and the planning process in a South African context - P. A. Miller; N. Binedell (South African Journal of Business Management, 1982)
The authors of this paper examine the extent of the application of environmental analysis during the planning process in South African businesses. Overseas, and in the United States in particular, sophisticated techniques for analysing the environment are being developed, and these would appear to have a ready market in the South African environment. Should South African business face relatively turbulent times in the near future, there will be a need for companies to develop effective means of analysing changing trends, and of integrating their findings into the strategic planning process. Two separate research surveys were conducted, one of 150 listed companies and a second of 15 major South African companies. While most journals and texts would see the environmental analysis as an integral part of the planning process, the majority of companies did not agree with this view.
Keywords: 650